2010
DOI: 10.1073/pnas.1001613107
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of retinoblastoma pathway inactivation dictates response to CDK4/6 inhibition in GBM

Abstract: Glioblastoma multiforme (GBM) is a fatal primary brain tumor harboring myriad genetic and epigenetic alterations. The recent multidimensional analysis of the GBM genome has provided a more complete view of the landscape of such alterations and their linked pathways. This effort has demonstrated that certain pathways are universally altered, but that the specific genetic events altered within each pathway can vary for each particular patient's tumor. With this atlas of genetic and epigenetic events, it now beco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
158
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 209 publications
(172 citation statements)
references
References 19 publications
14
158
0
Order By: Relevance
“…This was confirmed also in ex vivo studies on primary human tumor cultures [Dean et al 2012b]. CDK4 mutations [Young et al 2014], CDKN2A and CDKN2C (encoding p18 INK4C ) deletions [Wiedemeyer et al 2010] and low E2F expression [Logan et al 2013] have been shown to predict palbociclib response in other tumor types, whereas high expression of cyclin E1 [Konecny et al 2011] was associated with resistance.…”
Section: Cell Cycle and Endocrine Resistancesupporting
confidence: 55%
“…This was confirmed also in ex vivo studies on primary human tumor cultures [Dean et al 2012b]. CDK4 mutations [Young et al 2014], CDKN2A and CDKN2C (encoding p18 INK4C ) deletions [Wiedemeyer et al 2010] and low E2F expression [Logan et al 2013] have been shown to predict palbociclib response in other tumor types, whereas high expression of cyclin E1 [Konecny et al 2011] was associated with resistance.…”
Section: Cell Cycle and Endocrine Resistancesupporting
confidence: 55%
“…The CDK6 gene is frequently amplified or overexpressed in a variety of human cancers (Grossel and Hinds, 2006a), such as glioblastoma (Wiedemeyer et al, 2010), myxofibrosarcoma (Tsai et al, 2012), and lymphoid malignancies (Nagel et al, 2008). By accelerating progression through G1/S phase checkpoint of the cell cycle, overexpression of CDK6 increased cell proliferation and reduced DNA repair capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Since p16INK4a inhibits CDK4/6, which inactivates RB by phosphorylation, and since p19ARF (or P14ARF) targets MDM2, which suppresses p53 (5), we thus examined responses of modulating CDK4/6 and p53 in these cells. As shown in Figure 4E, inhibition of phosphorylation of RB, the direct downstream target of CDK4/6 by CDK4/6 inhibitor PD0332991 (20), markedly reduced PDGF-A-stimulated cell growth of Ink4a/Arf-deficient mAsts and LN444 cells in soft agar, which suggests that the tumorigenic effect of PDGFRα signaling is dependent on CDK4/6 inactivation of RB proteins (p-RB). Since we did not observe any tumor-suppressing effect of p19ARF on Ink4a/Arf -/-PDGFRα-expressing mAsts ( Figure 4B), we asked whether the downstream p53 protein was functional in these cells.…”
Section: Overexpression Of Pdgfrα And/or Pdgf-a Confers Tumorigenicitmentioning
confidence: 94%